Systemic right-to-left shunts, ischemic brain lesions, and persistent migraine activity. (3rd May 2016) - Koppen, Hille; Palm-Meinders, Inge H.; Mess, Werner H.; Keunen, Ruud W.; Terwindt, Gisela M.; Launer, Lenore J.; van Buchem, Mark A.; Kruit, Mark C.; Ferrari, Michel D.
Abstract : Objective: To assess whether migraine in the general population is associated with increased risk of systemic right-to-left shunts (RLS) and whether RLS are associated with increased prevalence of brain infarcts and persistent recurrence of migraine attacks at older age. Methods: Brain MRI and transcranial Doppler with air contrast in 166 unselected migraineurs (mean age ± SD 56 ± 7.7 years; 70% women; n = 96 migraine with aura) and 69 controls (mean age ± SD 55 ± 7.6 years; 65% women) from the general population. Results: Participants with migraine with aura more frequently had Valsalva-induced RLS (60%), in particular large-sized, compared to controls (42%; odds ratio [OR] 2.1; 95% confidence interval [CI] 1.1–3.9; p = 0.02) and participants with migraine without aura (40%; OR 2.3; 95% CI 1.2–4.3; p = 0.01). They also more frequently had spontaneous RLS (35%) than participants with migraine without aura (17%; OR 2.6; 95% CI 1.3–5.6; p = 0.01) but not compared to controls (26%; OR 1.6; 95% CI 0.8–3.1; p = 0.2). Participants with migraine with aura and spontaneous RLS more frequently had persistent migraine activity (85%) than participants with migraine without spontaneous RLS (63%; OR 3.4; 95% CI 1.2–10.1; p = 0.03). Nine percent of participants with RLS had silent posterior circulation infarcts compared to 3% of participants without RLS (OR 2.8; 95% CI 0.9–9.3; p = 0.08), independent of migraine status. RLS were not associated with white matter lesions. Conclusions: RLS are more prevalent in migraineurs with aura but do not explain the increased prevalence of silent posterior circulation infarcts or white matter lesions in migraineurs. Spontaneous RLS are associated with persistent migraine.